New lanthanoid biphenolate complexes, their further reactivity with trimethylaluminium and catalytic activity for the polymerisation of rac-lactide. Issue 41 (29th September 2021) - Shephard, Angus C. G.; Ali, Safaa H.; Wang, Jun; Guo, Zhifang; Davies, Murray S.; Deacon, Glen B.; Junk, Peter C.
Abstract : A series of rare earth biphenolate complexes of the general form [Ln(mbmp)(mbmpH)(thf)3 ] have been synthesised by redox transmetallation/protolysis (RTP) and assessed for ROP activity of rac -lactide. Abstract : A series of rare earth biphenolate complexes of the general form [Ln(mbmp)(mbmpH)(thf)3 ] (Ln = Y (1 ), Nd (2 ), Gd (3 ), Dy (4 ), Er (5 ), Tm (6 ) and Lu (7 )) have been synthesised by redox transmetallation/protolysis (RTP) from the free rare earth metal, Hg(C6 F5 )2 and 2, 2′-methylenebis(6- tert -butyl-4-methylphenol) (mbmpH2 ). The rare earth metal is six coordinate with one chelating biphenolate mbmp 2− ligand and one unidentate monophenolate mbmpH − ligand. The yttrium complex, when crystallised from hot toluene or deuterated benzene, loses a coordinated thf and exhibits coordination through all three phenolate oxygen atoms, as well as the oxygen of the phenol, yielding two solvates [Y(mbmp)(mbmpH)(thf)2 ]· n solv (solv = PhMe, n = 1 (8a ) or C6 D6, n = 2 (8b )). Of these rare earth complexes, the yttrium derivative (1 ) yielded the heterobimetallic complex [AlMe2 Y(mbmp)2 (thf)2 ] (9 ) when treated with trimethylaluminium, whereas all other complexes produced the transmetallation product [AlMe(mbmp)(thf)] (11 ). The dinuclear dysprosium complex [Dy2 (mbmp)3 (thf)3 ] (10 ) was isolated alongside 11 from the reaction of 4 with trimethylaluminium, suggesting trimethylaluminium instigates a redistribution reaction. The ROP activity of the mononuclear neodymium, dysprosium, lutetium, and aluminium complexes towards rac -lactide in toluene at 70 °C was found to be poor compared to rare earth complexes of monodentate aryloxides, but increased with increased rare earth ion size.